Le Bilan Sociétal© : de la prise en compte des intérêts contradictoires des parties prenantes à la responsabilité sociétale - Catherine Bodet; Dominique Picard (Développement Durable et Territoires)
The "Bilan Sociétal©" is in the same time an evaluation tool of corporate responsibility in terms of social and environmental development, and a progress processes to that end. One of its essential characteristics is the attention it gives to stakeholder's view. It begins by conducting their universal enquiries of questionnaire. This distinctive feature increases the reliability of the evaluation. It also increases the involvement of actors on social and environment, consequently strengthened a forward march to progress.